2018
DOI: 10.1007/s40614-018-00176-w
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Research with Planaria

Abstract: This article serves as a brief primer on planaria for behavior scientists. In the 1950s and 1960s, McConnell's planarian laboratory posited that conditioned behavior could transfer after regeneration, and through cannibalization of trained planaria. These studies, the responses, and replications have been collectively referred to as the "planarian controversy." Successful behavioral assays still require refinement with this organism, but they could add valuable insight into our conceptualization of memory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…For example, Perspectives on Behavior Science allows authors to archive online material (Hantula, 2016a(Hantula, , 2016b, including data protocols and software. Recent issues have included shared software (Bullock, Fisher, & Hagopian, 2017;Kaplan, Gilroy & Hursh, 2018) and video (Deochand, Costello, & Deochand, 2018). Other examples include publications that share software and protocols on public access platforms such as GitHub (e.g., Gilroy, Franck, & Hantula, 2017;Gilroy, Kaplan, Reed, Koffarnus, & Hantula, 2018).…”
Section: Encourage Open Sharing Of Research Protocols Software and mentioning
confidence: 99%
“…For example, Perspectives on Behavior Science allows authors to archive online material (Hantula, 2016a(Hantula, , 2016b, including data protocols and software. Recent issues have included shared software (Bullock, Fisher, & Hagopian, 2017;Kaplan, Gilroy & Hursh, 2018) and video (Deochand, Costello, & Deochand, 2018). Other examples include publications that share software and protocols on public access platforms such as GitHub (e.g., Gilroy, Franck, & Hantula, 2017;Gilroy, Kaplan, Reed, Koffarnus, & Hantula, 2018).…”
Section: Encourage Open Sharing Of Research Protocols Software and mentioning
confidence: 99%
“…PoBS has implemented these practices over the past few years and the options chosen by authors of articles in PoBS illustrate many of the choices available. For example, Springer can archive online supplementary material such as code (Bullock, Fisher, & Hagopian, 2017) and video (Deochand, Costello, & Deochand, 2018); materials may be archived in a university library (Kaplan et al, 2016) or on a public platform such as GitHub (Kaplan et al, 2019). It is readily recognized that using these kinds of repositories is a novel behavior for many behavior scientists and behavior analysts.…”
Section: Availability Of Data Protocols Code and Other Materialsmentioning
confidence: 99%
“…This is due to the high concentration of stem cells, around 25%, which are pluripotent neoblasts (Hammoudi et al, 2018). Once a worm is divided into two or more sections, each section develops into an independent organism but remains as a genetic clone (Deochand et al, 2018). Planaria have a very high regenerative capacity including their nervous system development.…”
Section: Introductionmentioning
confidence: 99%
“…However, controversies surround the memory transfer in planaria through cannibalism. These experiments were predominantly conducted by McConnell (1962) but were written off as myths and forgotten (Deochand et al, 2018). A few years later, another study suggested that memory could be transferred interspecifically when a wild planaria consumed a conditioned one (Ragland & Ragland, 1965).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation